2021
DOI: 10.1038/s41467-021-22762-4
|View full text |Cite
|
Sign up to set email alerts
|

Reductive evolution and unique predatory mode in the CPR bacterium Vampirococcus lugosii

Abstract: The Candidate Phyla Radiation (CPR) constitutes a large group of mostly uncultured bacterial lineages with small cell sizes and limited biosynthetic capabilities. They are thought to be symbionts of other organisms, but the nature of this symbiosis has been ascertained only for cultured Saccharibacteria, which are epibiotic parasites of other bacteria. Here, we study the biology and the genome of Vampirococcus lugosii, which becomes the first described species of Vampirococcus, a genus of epibiotic bacteria mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(137 citation statements)
references
References 62 publications
8
129
0
Order By: Relevance
“…Compared to Saccharibacteria, host relationships for Gracilibacteria and Absconditabacteria have received little attention. There are preliminary indications that Absconditabacteria may associate with members of the Fusobacteria or Firmicutes in the oral microbiome ( 45 ) or the gammaproteobacterium Halochromatium in certain salt lakes ( 86 ). We thus explored co-occurrence patterns in microbial communities containing Absconditabacteria and Gracilibacteria, attempting to further constrain possible host taxa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to Saccharibacteria, host relationships for Gracilibacteria and Absconditabacteria have received little attention. There are preliminary indications that Absconditabacteria may associate with members of the Fusobacteria or Firmicutes in the oral microbiome ( 45 ) or the gammaproteobacterium Halochromatium in certain salt lakes ( 86 ). We thus explored co-occurrence patterns in microbial communities containing Absconditabacteria and Gracilibacteria, attempting to further constrain possible host taxa.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, changes in abundance over a sample series from a bioreactor system treating thiocyanate were recently used to suggest that Microbacterium ginsengisoli may serve as a host for a cooccurring Saccharibacteria bacterium ( 56 ). One Absconditabacteria lineage ( Vampirococcus ) has been predicted to have a host from the Gammaproteobacteria ( 86 ), and one Gracilibacteria was suggested to have a Colwellia host based on a shared repeat protein motif ( 14 ). Given the scant information about possible hosts for these CPR bacteria, especially for Absconditabacteria and Gracilibacteria, the patterns of co-occurrence we report for specific organisms provide starting points for host identification via targeted coisolation.…”
Section: Discussionmentioning
confidence: 99%
“…One major lineage of the domain Bacteria, Patescibacteria (also known as Candidate Phyla Radiation/CPR) [1,2], is a highly diverse group of bacteria, widely inhabiting [3,4] natural and artificial ecosystems [5,6], characterized with small cell/genome size [7] and poor (genomically predicted) abilities to synthesize cellular building blocks [4] suggestive of symbiotic dependency for cell growth. Most members remain uncultured, leaving major knowledge gaps in the range and nature of their symbioses, but several cultivation-based studies have demonstrated host-specific symbiotic/parasitic interactions between Patescibacteria and other bacteria [8][9][10][11]. This pointed towards specialization towards bacteria-bacteria symbioses, especially given parallels with DPANN, an archaeal analog who has only been observed to interact with other archaea [4,12]; however, one study has reported Patescibacteria-eukarya symbiosis [13], indicating that the Patescibacteria host range reaches beyond bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recently cultured environmental TM7 bacteria were found to have Actinobacteria hosts ( 10 ). However, Absconditabacteria , another phylum within the CPR, were recently found to associate with non- Actinobacteria hosts of the genus Halochromatium ( Gammaproteobacteria , Chromatiaceae ) ( 36 ). This observation raises several intriguing possibilities: (i) actinobacterial association may be a synapomorphy of TM7 relative to other CPR and (ii) non-actinobacterial hosts remain to be discovered for uncultivated TM7, especially from other divergent groups ( 14 ).…”
Section: Discussionmentioning
confidence: 99%